Implementasi Kontrol Kecepatan Motor DC pada Sistem Pemotong Pita Otomatis menggunakan Mikrokontroler : Implementasi Kontrol Kecepatan Motor DC pada Sistem Pemotong Pita Otomatis menggunakan Mikrokontroler - Imam Saukani; Agus Sukoco Heru Sumarno; Achmad Zaini; Prasetyo Hermawan (Politeknik Negeri Malang, 2026)
This study presents the design and implementation of an automatic ribbon cutting system aimed at enhancing precision and efficiency in small and medium enterprise (SME) production processes. The system employs an ESP32 microcontroller, a rotary encoder, and a DC motor governed by a proportional–integral–derivative (PID) control algorithm to maintain consistent cutting lengths. Experimental evaluations were conducted for setpoint lengths ranging from 50 to 100 cm at 5 cm intervals. PID parameters were systematically optimized, with a proportional gain of Kp = 0.03 achieving the lowest mean error of ±0.2 cm. Results indicate a substantial improvement in cutting accuracy compared to operations without PID control, with typical error tolerances ≤1 cm. This paper details the mechanical design, control system architecture, PID tuning methodology, and experimental performance analysis. The primary contribution lies in demonstrating the integration of PID control in an accessible and replicable ribbon cutting system suitable for SME applications.